Path to the EU: protection and support for crime victims - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2024)
The ECJ Burden Case and Ukrainian Path to Victim Protection legislation are analyzed On the one hand, the EU has already adopted a robust set of legislation on victims' rights. On the other, - UA faced the challenge of not rejecting but adopting UA Law on compensating victims of crime. These are urgent issues of transitional justice that must be addressed. Проаналізовано справу ЄС про тягар та український шлях до захисту потерпілих. З одного боку, ЄС уже прийняв потужний пакет законодавства щодо прав потерпілих. З іншого боку, перед Україною постало завдання не відхилити, а прийняти Закон України про компенсацію жертвам злочинів. Це нагальні питання правосуддя перехідного періоду, які необхідно вирішити.
Tuliakov V. O. Path to the EU: protection and support for crime victims // ResearchGate. - preprint. - 2024. - 5 р. Режим доступу: DOI:10.13140/RG.2.2.10974.65608
Keywords: компенсації жертвам злочинів; Директива ЄС; італійський суд; пакет законодавства про права жертв; Стратегія ЄС щодо прав жертв (2020–2025); Положення Закону України «Про забезпечення прав та Свободи громадян і правовий режим на тимчасово окупованих територіях України»; Європейська Конвенція про компенсацію жертвам насильницьких злочинів; Європейський суд з прав людини; compensation to crime victims; EU Directive; Italian court; victims' rights package; EU Victims' Rights Strategy (2020–2025); Provisions of the Law of Ukraine "On Ensuring the Rights and Freedoms of Citizens and the Legal Regime in the Temporarily Occupied Territories of Ukraine"; European Convention on Compensation to Victims of Violent Crimes; European Court of Human Rights